Differential Analysis in Ultra Micro Business: The role of Activity Based Costing - Frida Fanani Rohma; Habi Bullah; Khy'sh Nusri Leapatra Chamalinda; Auliya Zulfatillah (Journal of Sharia Economics, Banking and Accounting, 2025)
Production costs are a part of determining the cost of goods that can affect the amount of profit generated by the company. The development of research is still limited to an effort to consider several traditional counting techniques, differential analysis and Activity Based Costing (ABC) separately. This study seeks to explore the role of differential analysis using the Activity Based Costing (ABC) method in the simultaneous analysis mechanism. This study uses a qualitative method. This research uses Ultra Micro Based on initial observations, it is shown that the understanding of the management of cost information is still very limited. Thus, an exploration was carried out by facilitating the preparation of a differential analysis by elaborating activity-based costing in the system for determining the cost of production. The results showed that the application of differential costs as the basis for making special orders decisions was to add up all production costs, variable costs and fixed costs. The profit obtained is greater than the profit obtained without a special order and the best alternative used by the company in making decisions is receiving from customers.